Bullying dan dampak jangka panjang koneksi dengan kekerasan dan kriminalitas - Rachmawati, Dian (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2024)
Cases of bullying often occur in Indonesia, especially in school environments, and can hinder students' learning processes. This research uses a literature study approach to investigate basic theories, characteristics, factors, divisions, and roles in the problem of bullying. The definition of bullying, as expressed by Olweus (1999), refers to a psychosocial issue where someone repeatedly mocks and demeans another person, with negative impacts felt by both parties, namely the perpetrator and the victim. Bullying often involves a power imbalance, where the perpetrator has greater power than the victim. With advances in technology, bullying not only occurs in person, but also involves social media platforms. Efforts to overcome the impact of bullying and reduce bullying rates can be carried out by educational practitioners through various intervention programmes. This programme involves various parties, such as parents, peers, educators, school counsellors, school administrators, and all members of the school community. Bullying is oppressive treatment towards other people. Bullying as a form of aggressive action is a global problem, one of which is in Indonesia. Currently, the educational environment has seen a lot of bullying behaviour occur. Bullying behaviour usually starts in childhood because, at this time, children are required to be able to adapt themselves to their peers. There are several factors that can influence bullying, namely family factors, peer factors, and school factors.